Using UNPRME to Teach, Research, and Enact Business Ethics: Insights from the Catholic Identity Matrix for Business Schools - Goodpaster, Kenneth E. (Journal of business ethics, 2018)
We address how the leaders of a Catholic business school can articulate and assess how well their schools implement the following six principles drawn from Catholic social teaching (CST): (1) produce goods and services that are authentically good; (2) foster solidarity with the poor by serving deprived and marginalized populations; (3) advance the dignity of human work as a calling; (4) exercise subsidiarity; (5) promote responsible stewardship over resources; and (6) acquire and allocate resources justly. We first discuss how the CST principles give substantive content and meaning to the Good Goods, Good Work, and Good Wealth framework in The Vocation of the Business Leader (Pontifical Council for Justice and Peace in Vocation of the business leader, Pontifical Council for Justice and Peace, Vatican City, 2012) and then discuss their congruencies and tensions with the UNGC and UNPRME principles. Next, we describe the Catholic Identity Matrix, an assessment tool that provides a quantitative and qualitative portrait of how well a Catholic business school integrates, within the scope of its mission and capacities, the three goods and related CST principles in its strategies, policies, activities, and processes. The concluding section discusses implications for ongoing UNGC and UNPRME assessment, reporting, and development efforts, and addresses the generalizability of our approach to business schools who draw their inspiration and moral principles from other faith-based or secular traditions.